PENGARUH KEGIATAN BERCERITA DENGAN BUKU CERITA ISLAMI TERHADAP PERILAKU MORAL ANAK - Susanti, Meryl Dwi (JIV-Jurnal Ilmiah Visi, 2013)
This study aims to obtain empirical data on the effects of storytelling activities with Islamic books on moral behavior of the children aged 5-6 years in Unwanul Khairiyah RA and RA Nurul Akbar. The research method used was ex post facto. The research samples were 20 children selected by simple random sampling. The techniques of data analysis conducted prior to the test requirements consisted of normality and homogeneity. This study concluded that there are significant positive storytelling activities with Islamic books on moral behavior of the children aged 5-6 years. The implications of the results of the study are that teachers should create learning activities that can develop the children’s moral behavior in a joyful method such as story telling with Islamic books. The teachers also need to be more creative in using methods and media.